The Illusion of Perfect Ownership: Evaluating Digital Gold via Maqāṣid al-Sharīʿah - Ratih Farhani Avisya; Yasni Efyanti; Yudesman Yudesman (Al-Qisthu, 2025)
The expansion of digital financial technologies has shifted gold ownership from physical possession into electronically recorded claims, challenging classical Islamic legal concepts of ownership (al-milk) and possession (qabḍ). This study aims to evaluate the substantive quality of digital gold ownership through the lens of maqāṣid al-sharīʿah, focusing specifically on the protection of wealth (ḥifẓ al-māl). Employing a qualitative, normative-doctrinal, and analytical design, this research examines contemporary Indonesian regulatory frameworks, Shariah fatwas, and the structural-operational features of Bank Syariah Indonesia (BSI) as a typified case illustration. The findings reveal that digital gold structures in Islamic banking represent an access-based ownership model where the material existence of the asset is fulfilled, yet individual traceability and effective control remain institutionally constrained. Consequently, digital gold ownership is characterized as partial—robust as an abstract economic value representation but fragile at the physical underlying asset level, thereby challenging the realization of milk tāmm (complete ownership). This study offers a novel theoretical framework by shifting the Shariah assessment of digital financial innovations from mere formal-contractual compliance to the substantive density of access-based ownership designs in practice.